Meta-Analysis of Susceptibility of Woody Plants to Loss of Genetic Diversity through Habitat Fragmentation - VRANCKX, GUY; JACQUEMYN, HANS; MUYS, BART; HONNAY, OLIVIER (Conservation biology, 2012)
Shrubs and trees are assumed less likely to lose genetic variation in response to habitat fragmentation because they have certain life-history characteristics such as long lifespans and extensive pollen flow. To test this assumption, we conducted a meta-analysis with data on 97 woody plant species derived from 98 studies of habitat fragmentation. We measured the weighted response of four different measures of population-level genetic diversity to habitat fragmentation with Hedge's d and Spearman rank correlation.We tested whether the genetic response to habitat fragmentation was mediated by life-history traits (longevity, pollination mode, and seed dispersal vector) and study characteristics (genetic marker and plant material used). For both tests of effect size habitat fragmentation was associated with a substantial decrease in expected heterozygosity, number of alleles, and percentage of polymorphic loci, whereas the population inbreeding coefficient was not associated with these measures. The largest proportion of variation among effect sizes was explained by pollination mechanism and by the age of the tissue (progeny or adult) that was genotyped. Our primary finding was that wind-pollinated trees and shrubs appeared to be as likely to lose genetic variation as insect-pollinated species, indicating that severe habitat fragmentation may lead to pollen limitation and limited gene flow. In comparison with results of previous meta-analyses on mainly herbaceous species, we found trees and shrubs were as likely to have negative genetic responses to habitat fragmentation as herbaceous species. We also found that the genetic variation in offspring was generally less than that of adult trees, which is evidence of a genetic extinction debt and probably reflects the genetic diversity of the historical, less-fragmented landscape. Se asume que los arbustos y hierbas tienen menos probabilidad de perder variación genética como respuesta a la fragmentación del habitat porque su historia de vida tiene ciertas características como longevidad y flujo extensivo de polen. Para probar esta suposición, realizamos un meta-análisis con datos de 97 especies de plantas leñosas derivados de 97 estudios de fragmentación del habitat. Medimos la respuesta ponderada de cuatro medidas diferentes de diversidad genética a nivel población con fragmentación de habitat mediante correlación d de Hedge y de rangos de Spearman. Probamos si la respuesta genética a la fragmentación del habitat estaba mediada por los atributos de la historia de vida (longevidad, forma de polinización y vector dispersor de semillas) y características de estudio (marcador genético y material vegetal utilizado). Para ambas pruebas del efecto del tamaño, la fragmentación del hábitat se asoció con un decremento sustancial de la heterocigosidad esperada, el número de alelosy el porcentaje de loci polimórfico, mientras que el coeficiente de endogamia no se asoció con esas medidas. La mayor proporción de variación entre los tamaños de efecto se explicó por el mecanismo de polinización y por la edad del tejido (progenie o adulto) que fue genotipado. Nuestro hallazgo primario fue que los árboles y arbustos polinizados por viento aparentemente tuvieron la misma probabilidad de perder variación genética que las especies polinizadas por insectos, lo que indica que la fragmentación de hábitat severa puede llevar a una limitación de polen y en el flujo de genes. En comparación con resultados de meta-análisis previos, principalmente de especies herbáceas, encontramos que árboles y arbustos tenían la misma probabilidad que las especies herbáceas de tener respuestas genéticas negativas a la fragmentación del habitat. También encontramos que la variación genética de la descendencia generalmente fue menor que la de árboles adultos, lo cual es evidencia de una deuda de extinción genética y probablemente refleja la diversidad genética del paisaje histórico, menos fragmentado.